Improvement in oxidative stress and antioxidant parameters in β-thalassemia/Hb E patients treated with curcuminoids - Kalpravidh R. (2017)
Objectives: To evaluate the hematological profile, oxidative stress, and antioxidant parameters in β-thalassemia/Hb E patients treated with curcuminoids for 12 months. Design and methods: Twenty-one β-thalassemia/Hb E patients were given 2 capsules of 250 mg each of curcuminoids (a total of 500 mg) daily for 12 months. Blood was collected every 2 months during treatment and 3 months after withdrawal and was determined for complete blood count, malonyldialdehyde (MDA), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), reduced glutathione (GSH) in red blood cells (RBC), and non-transferrin bound iron (NTBI) in serum. Results: The increased oxidative stress in β-thalassemia/Hb E patients was shown by higher levels of MDA, SOD, GSH-Px in RBC, serum NTBI, and lower level of RBC GSH. Curcuminoids administration resulted in improvement of all the measured parameters as long as they were administered. After 3 months withdrawal of treatment, all parameters returned close to baseline levels. Conclusion: Curcuminoids may be used to ameliorate oxidative damage in patients with β-thalassemia/Hb E disease. © 2009 The Canadian Society of Clinical Chemists.